2015
DOI: 10.1080/21623945.2015.1027848
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced remodeling of the adipose tissue elastin network is independent of the metalloelastase MMP-12

Abstract: The extracellular matrix (ECM) plays important roles in maintaining adequate adipose tissue function and in metabolic regulation. Here we have examined the organization of a relatively unexplored adipose tissue ECM component, elastin and its response to diet induced obesity in mice. Additionally, we have explored the regulation and requirement of macrophage metalloelastase, MMP-12, in adipose tissue ECM remodeling in obesity. In visceral fat depots, elastin fibers form a mesh-like net that becomes denser with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 36 publications
2
35
1
1
Order By: Relevance
“…MMP12 (macrophage elastase) is the major MMP that degrades elastin in mice [57]. In HFD (60% fat)-induced obesity, adipose macrophages, particularly CD11c − residential macrophages (M2-like) express a high level of MMP12 [58,59]. In their study, the loss of MMP12 exacerbated HFD-induced adipose hypertrophy but improved insulin sensitivity [58].…”
Section: Ecm Modifiers In the Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…MMP12 (macrophage elastase) is the major MMP that degrades elastin in mice [57]. In HFD (60% fat)-induced obesity, adipose macrophages, particularly CD11c − residential macrophages (M2-like) express a high level of MMP12 [58,59]. In their study, the loss of MMP12 exacerbated HFD-induced adipose hypertrophy but improved insulin sensitivity [58].…”
Section: Ecm Modifiers In the Adipose Tissuementioning
confidence: 99%
“…In their study, the loss of MMP12 exacerbated HFD-induced adipose hypertrophy but improved insulin sensitivity [58]. The loss of MMP12 alone, however, did not change elastin content in adipose tissues under either normal or HFD condition [59]. Another group reported that the loss of MMP12 did not exert any significant effects on HFD (42% fat)-induced obesity [60].…”
Section: Ecm Modifiers In the Adipose Tissuementioning
confidence: 99%
“…Therefore, the high flexibility of ECM, as well as the adequate balance between the ECM deposition and degradation, ensures that the healthy expansion of adipose tissue occurs (Trayhurn ; Martinez‐Santibanez et al . ; Choe et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…MMPs cooperate in this process (Mariman & Wang 2010). Therefore, the high flexibility of ECM, as well as the adequate balance between the ECM deposition and degradation, ensures that the healthy expansion of adipose tissue occurs (Trayhurn 2013;Martinez-Santibanez et al 2015;Choe et al 2016). On the other hand, the excessive increase in adipose tissue leads to hypoxia of the tissue that induces ECM fibrosis with a consequent reduction in the tissue plasticity, which triggers the adipose tissue metabolic dysfunction (Trayhurn 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(22) Elastin is one of the major substrates of active MMP12, but it was recently shown that remodeling of the elastin network during obesity is independent of MMP12. (43) Hence, the functional impact of active MMP12 in cardiometabolic disease appears to involve other substrates. MMP12 is able to cleave other molecules, including OPN (Supplementary Figure S1).…”
Section: Acknowledgmentsmentioning
confidence: 99%